Rehabilitation Methods for Patients with Geographic Atrophy due to Age-Related Macular Degeneration and Effects of Rehabilitation on Quality of Life - Damla Erginturk Acar; Figen Batioglu; Aysun Idil; Esra Sahli; Dincer Goksuluk (Journal of Ophthalmology)
Purpose. The purpose of the study is to evaluate the low vision rehabilitation methods and to investigate the effect of visual rehabilitation on quality of life in patients with low vision due to geographic atrophy from age-related macular degeneration (ARMD). Methods. The better-seeing eye of 78 patients with geographic atrophy due to ARMD were included in the study. Sociodemographic characteristics, ophthalmological examination findings, and preferred low vision aids for near and distant were recorded. Fifty-seven patients who preferred to use a low vision aid device in daily life were considered as a rehabilitation group, whereas 21 patients who did not use any device were considered as a control group. The National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) was applied to all patients at the initial examination and at least 6 months after the initial examination. Results. In the rehabilitation group, statistically significant increases were found in the overall composite score, and general vision, near and distance activities, social functioning, mental health, role difficulties, and dependency subscale scores of the NEI-VFQ-25 quality of life scale after low vision rehabilitation (p=0.009 for general vision, p<0.001; for others). In the control group, there was no statistically significant change in any of the subscale scores or the overall score of the scale (p>0.05). All patients (n = 78) were recommended to use at least one low vision aid for near vision. Hyperocular glasses were recommended for 77 patients (98.72%), magnifiers for 15 patients (19.23%), electro-optical devices for 2 patients (2.56%), and telemicroscope for one patient (1.28%). Furthermore, 17 patients (21.8%) were prescribed more than one low vision aids. However, for distance vision, only 29 patients (37.18%) received a recommendation for a low vision aid. Conclusions. Low vision patients with ARMD-related geographic atrophy should meet with low vision aids as soon as possible and should be included in low vision rehabilitation programs.